Bankruptcy Profile of Foreign vs. Domestic Islamic Banks of Malaysia: A Post Crisis Period Analysis - Jan, Amin; Marimuthu, Maran (International Journal of Economics and Financial Issues, 2016)
After the (2007-2008) subprime financial crisis considering bankruptcy evaluation for the banking industry becomes a paramount. In line of that, this study aims to analyze the bankruptcy profile of foreign vs. domestic Islamic banks in Malaysia. This study predicted 40 percent and 75 percent bankruptcy in the subjected samples of foreign and domestic Islamic banks of Malaysia respectively. However, the specific reason behind this variation in their bankruptcy rates is tagged with the significant difference in liquidity ratio i.e. (1.59) by foreign and (0.41) by the domestic Islamic banks sample. The ANOVA results revealed that, the sample of foreign and domestic Islamic banks of Malaysia do differ significantly on bankruptcy rates as well as on the top bankruptcy's predictors namely liquidity, profitability, and insolvency. However, the sample does not vary on productivity with regards to bankruptcy exposure. Furthermore, the regression results revealed that, liquidity, profitability, and insolvency ratios in the sample of domestic Islamic banks, while only insolvency ratio in the sample of foreign Islamic banks have a significant positive relationship with bankruptcy in Islamic banking industry of Malaysia. Moreover, in the context of identified bankruptcy rates, the analysis here is viable to witness the sustainability ratings possessed by the sample of foreign and domestic Islamic banks of Malaysia. Keywords: Bankruptcy, Sustainability, Foreign Islamic Banks, Domestic Islamic Banks, Financial Characteristics JEL Classifications: A10, C01, C12, C33, C50, C53